Development and validation of the internet gaming disorder scale-9 short form Japanese version for children for early screening in elementary school children - Ogiso, Azusa; Inoue, Takeshi; Kitajima, Tasuku; Ujiie, Yuta; Oto, Yuji; Sakuta, Ryoichi (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionThe increasing use of digital devices has led to growing concern over Internet Gaming Disorder (IGD) among younger children. While several tools for the assessment of IGD have been developed, validated questionnaires have primarily been designed for children aged nine years and older, leaving a gap for early detection. This study developed and validated the Internet Gaming Disorder Scale-9 Short Form Japanese version for Children (IGDS9-SF-JC), a self-reported screening tool tailored for lower elementary school children.MethodsThe IGDS9-SF-JC was developed in collaboration with pediatric neurologists, child and adolescent psychiatrists, clinical psychologists, and elementary school teachers. This study assessed 525 children aged 6–12 years studying at a public elementary school in Chiba Prefecture, Japan.ResultsThe IGDS9-SF-JC demonstrated high internal consistency (Cronbach's α = 0.849). Confirmatory factor analysis indicated a unidimensional structure with acceptable model fit indices (GFI = 0.942, CFI = 0.931, RMSEA = 0.085). In general, boys had significantly higher total scores than girls, and higher scores were associated with ownership of a gaming device and/or a smartphone, longer times spent gaming and video-watching, later bedtimes, and skipping breakfast. These results are consistent with previous findings of IGD and lifestyle factors in older children and adolescents.DiscussionThe IGDS9-SF-JC expands the applicability of IGD screening to younger children, providing a reliable and valid tool for the early identification and potential intervention of IGD. Further studies are required to refine the instrument and establish clinical cutoff scores using comparison with clinical populations.